1997
DOI: 10.1016/s0014-5793(97)00127-0
|View full text |Cite
|
Sign up to set email alerts
|

Swine influenza virus strains recognize sialylsugar chains containing the molecular species of sialic acid predominantly present in the swine tracheal epithelium

Abstract: We determined the ratio of A'-glycolylneuraminic acid (Neu5Gc) to TV-acetylneuraminic acid (Neu5Ac) in swine respiratory epithelia by fluorometric high-performance liquid chromatography, and examined the binding specificity of swine influenza virus strains for gangliosides containing different molecular species of sialic acid (Neu5Ac and Neu5Gc), and for bovine erythrocyte sialoglycoprotein 2 (GP-2) containing Neu5Gc as its predominate sialic acid (96% of total sialic acids). The presence of Neu5Gc, which had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 25 publications
(14 reference statements)
3
79
0
Order By: Relevance
“…The present work is the first study to show, by using a reverse genetics system, that not only residue 155 but also residue 158 in the HA protein contributes to the recognition of molecular species of sialic acid. In the transmission of IAVs between ducks and other animals including pigs, glycoconjugates containing Neu5Gc in the trachea of the pig and crypt cells of the duck colon may be utilized as a common receptor that avian, swine, and equine IAV can recognize [1,6,14,17]. Our finding will be helpful in understanding the significance of molecular species of sialic acid for viral transmission, host range restriction, and pandemics, leading to useful information for the development of anti-influenza virus agents and surveillance of pandemic potential.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present work is the first study to show, by using a reverse genetics system, that not only residue 155 but also residue 158 in the HA protein contributes to the recognition of molecular species of sialic acid. In the transmission of IAVs between ducks and other animals including pigs, glycoconjugates containing Neu5Gc in the trachea of the pig and crypt cells of the duck colon may be utilized as a common receptor that avian, swine, and equine IAV can recognize [1,6,14,17]. Our finding will be helpful in understanding the significance of molecular species of sialic acid for viral transmission, host range restriction, and pandemics, leading to useful information for the development of anti-influenza virus agents and surveillance of pandemic potential.…”
Section: Resultsmentioning
confidence: 99%
“…The plates were then incubated with rabbit anti-IAV antibodies for 2 h at 4°C, followed by horseradish peroxidase-conjugated protein A. Finally, the plates were visualized as described in [1]. After washing with 0.01% Tween20-PBS, the wells were incubated with 50 ll/well of IAV suspension (2 10 HAU) at 4°C for 12 h. After washing, the wells were incubated with mouse anti-HA MAb, followed by horseradish peroxidase-conjugated anti-mouse IgG + M. Finally, the wells were colored as described in [12].…”
Section: Virus Overlay Assaymentioning
confidence: 99%
“…Suzuki et al. 15 reported that swine tracheal epithelia have Neu5Gc as the terminal sialic acid residue, which had not been detected in human tracheal epithelia along with Neu5Ac, and SIVs preferentially bind Neu5Gc compared with human viruses.…”
mentioning
confidence: 98%
“…Some Sia-binding proteins can distinguish Neu5Gc from Neu5Ac. Thus, the CMAH mutation could have altered interactions involving endogenous human receptors such as sialoadhesin͞Siglec-1 (10) and myelin-associated glycoprotein͞Siglec-4a (11), as well as the binding of pathogenic microorganisms such as influenza A (12)(13)(14), rotaviruses (15), and Escherichia coli K99 (16). Such differences could have potentially affected human ontogeny, physiology, disease susceptibility, and͞or the ability of humans to domesticate livestock.…”
mentioning
confidence: 99%